Small is beautiful: demystifying and simplifying standard operating procedures: a model from the ethics review and consultancy committee of the Cameroon Bioethics Initiative - Ouwe Missi Oukem-Boyer, Odile; Munung, Nchangwi Syntia; Tangwa, Godfrey B. (BMC medical ethics, 2016)
Research ethics review is a critical aspect of the research governance framework for human subjects research. This usually requires that research protocols be submitted to a research ethics committee (REC) for review and approval. This has led to very rapid developments in the domain of research ethics, as RECs proliferate all over the globe in rhyme with the explosion in human subjects research. The work of RECs has increasingly become elaborate, complex, and in many cases urgent, necessitating supporting rules and procedures of operation. Guidelines for elaborating standard operating procedures (SOPs) for the functioning of RECs have also been proposed. The SOPs of well-placed and well-resourced RECs have tended to pay much attention to details, resulting, as a consequence, in generally long, elaborate, intricate and complex SOPs; a model that can hardly be replicated by other committees, equally under ethics review pressures, but working under much more constraining conditions in resource-destitute environments. In this paper, we looked at the content and length of SOPs from African RECs and compared them to the World Health Organization (WHO)'s guidelines as the gold standard. We also looked at the SOPs from the Ethics Review and Consultancy Committee (ERCC) of the Cameroon Bioethics Initiative that we elaborated in a simplified way in 2013, and compared them to the WHO's guidelines and to the other SOPs. Sixteen SOPs from 14 African countries were collected from various sources. Their average length was of 30 pages. By comparison to the guidance of the WHO, only six of them were found acceptable with more than 70 % of the criteria from the gold standard that were fully described. Among those six, two of them were very long and detailed (65 and 102 pages), while the four remaining SOPs ranged from 16 to 24 pages. The ERCC SOPs are seven pages long but maintain all that is of essence for the rigorous, efficient and timely review of protocols. We are convinced that, because of their brevity, simplicity, clarity and user-friendliness, the ERCC SOPs recommend themselves as a model template to, at least, committees similarly situated and/or circumstanced as the ERCC of the Cameroon Bioethics Initiative is. In fact, brevity, clarity, simplicity and user-friendliness are recognized values. Whatever is brief and clear is better than what is not and saves time. What is simple and user-friendly is better than what is not even though the two have the same aims because it saves both time and mental energy. And if this be true in general, it is even truer of the context and its peculiar constraints that we are addressing.